1991
DOI: 10.1097/00000658-199104000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Early Gastric Cancer Twenty-eight-Year Experience

Abstract: A retrospective study of early gastric cancer (60 patients) was performed to evaluate its diagnosis and treatment. Ninety-five per cent of patients presented with nonspecific gastrointestinal symptoms and 53.3% had been treated for presumed benign disease for up to 48 months before diagnosis. Fiberoptic endoscopy detected these lesions more accurately than radiologic examination. The disease-free 5-year survival rate after resection was 76.4%. Survival showed no significant correlation with sex, tumor site, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
2
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 12 publications
5
37
2
1
Order By: Relevance
“…Similar to findings in other European [14] and in North-American [28] and Japanese [10,25,34] series, we found that most lesions (63.8%) were of the depressed or excavated types. Also, as reported previously [8,14], protruded tumors (type I and IIa) were mostly differentiated intestinal type carcinomas (72%), whereas depressed or excavated types displayed both diffuse and intestinal patterns.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to findings in other European [14] and in North-American [28] and Japanese [10,25,34] series, we found that most lesions (63.8%) were of the depressed or excavated types. Also, as reported previously [8,14], protruded tumors (type I and IIa) were mostly differentiated intestinal type carcinomas (72%), whereas depressed or excavated types displayed both diffuse and intestinal patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Recurrence rates of 16% [14,28] and 34% [32] have been reported in Western countries, significantly higher than that reported by Japanese authoris [35,36].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Conversely, AGC progressively penetrates the muscularis propria or the subserosa, the serosa and the adjacent structures (Kajitani, 1981;Wang et al, 1997). In EGC, prognosis is favorable, after gastrectomy and lymph node dissection, accounting for 5-and 10-year survival rates of 90 and 85-90%, respectively, compared with 20-30% in AGC (Lawrence and Shiu, 1991;Dicken et al, 2005). Therefore, great attention has been directed to early detection in countries where gastric carcinoma is prevalent, such as Japan and Korea (Henderson, 1990;Parkin, 2004).…”
Section: Introductionmentioning
confidence: 99%